On the predictive validity of behavioral momentum theory for mitigating resurgence of problem behavior. Issue 1 (30th January 2018) - Fisher, Wayne W.; Greer, Brian D.; Craig, Andrew R.; Retzlaff, Billie J.; Fuhrman, Ashley M.; Lichtblau, Katherine R.; Saini, Valdeep
Abstract : We summarize the results of four recent translational studies from our lab that used the predictions of behavioral momentum theory to inform the development of more durable treatments for destructive behavior. Treatments informed by behavioral momentum theory generally showed better suppression of target responding during an extinction challenge than did a comparison treatment. We reanalyze data from each of the four studies to show that this general finding is apparent both at the aggregate (i.e., proportion of baseline response rates averaged across participants) and within participant (i.e., percentage reduction in proportion of baseline response rates, difference in raw response rates during the extinction challenge). Interestingly, participants who experienced multiple cycles of the extinction challenge generally showed less differentiation in target responding between the treatment informed by behavioral momentum theory and the comparison treatment. Overall results suggest that applications of behavioral momentum theory can substantially improve the durability of common treatments for destructive behavior.